Dyestuffs for Wood Stains - General Dyestuff Corporation; Interessengemeinschaft Farbenindustrie Aktiengesellschaft (1900)
Sample book for dyeing solutions on wood from the Interessengemeinschaft Farbenindustrie Aktiengesellschaft, a German chemical and pharmaceutical conglomerate. Contains dyeing instructions and sixty-four mounted wood samples on accordion-folded pages. Digital content includes all pages and a representative image of the full foldout.
Keywords: Dyes and dyeing--Equipment and supplies; Sample books; Stains and staining; Dyes and dyeing